Associations of Self-Reported Race, Social Determinants of Health, and Polygenic Risk With Coronary Heart Disease - Norland, Kristjan; Schaid, Daniel J; Naderian, Mohammadreza; Na, Jie; Kullo, Iftikhar J (Journal of the American College of Cardiology, 2024)
Social determinants of health (SDOH) influence the risk of common diseases such as coronary heart disease (CHD). This study sought to test the associations of self-reported race/ethnicity, SDOH, and a polygenic risk score (PRS), with CHD in a large and diverse U.S. In 67,256 All of Us (AoU) participants with available SDOH and whole-genome sequencing data, we ascertained self-reported race/ethnicity and 22 SDOH measures across 5 SDOH domains, and we calculated a PRS for CHD (PRS , PGS004696). We developed an SDOH score for CHD (SDOH ). We tested the associations of SDOH and PRS with CHD in regression models that included clinical risk factors. SDOH across 5 domains, including food insecurity, income, educational attainment, health literacy, neighborhood disorder, and loneliness, were associated with CHD. SDOH was highest in self-reported Black and Hispanic people. Self-reporting as Blacks had higher odds of having CHD than Whites but not after adjustment for SDOH . SDOH and PRS were weakly correlated. In the test set (n = 33,628), 1-SD increases in SDOH and PRS were associated with CHD in models that adjusted for clinical risk factors (OR: 1.32; 95% CI: 1.23-1.41 and OR: 1.36; 95% CI: 1.28-1.44, respectively). SDOH and PRS were associated with incident CHD events (n = 52) over a median follow-up of 214 days (Q1-Q3: 88 days). Increased odds of CHD in people who self-report as Black are likely due to a higher SDOH burden. SDOH and PRS were independently associated with CHD. Our findings suggest that including both PRS and SDOH in CHD risk models could improve their accuracy.